Characteristics of Friction Stir Welding of 3 mm thick ABS and PC thermoplastic polymers: An experimental approach - Shaheer Ahmed Khan; Muhammad Sohail (PLoS ONE, 2025)
The utilization of thermoplastics is extensively prevalent in modern industrial sectors owing to their distinctive mechanical features. Friction stir welding is recognized as a distinctive joining technology that addresses the weaknesses of heat-induced fusion welding. This friction-stirred solid-state welding technology can be effectively employed to join various difficult-to-weld polymeric materials. This paper examines the weldability of friction stir butt welding utilizing a cylindrical tapered threaded tool on a 3 mm thick Acrylonitrile Butadiene Styrene (ABS) and Polycarbonate (PC) polymers. The impact of tool rotational speed (800 and 1200 rpm) and tool traverse speed (10 mm/min to 50 mm/min) on the joint strength of welded samples has been analyzed. The maximum joint efficiency achieved is 52.71% for ABS while using a rotational speed of 1200 RPM and a traverse speed of 10 mm/min. For PC, the maximum joint efficiency is 54% with a rotational speed of 800 RPM and a traverse speed of 40 mm/min. The joint efficiency of polymer is significantly improved as a result of the effective heat distribution and fusion during the welding. The tensile strength of ABS polymer decreases as the traverse speed increases from 10 mm/min to 50 mm/min at both rotational speeds of 800 and 1200 rpm. However, the tensile strength of PC polymer exhibits fluctuations as the traverse speed increases from 10 mm/min to 50 mm/min. This behavior may be attributed to the fluctuating heating and cooling conditions that occur during the welding process at varying rotation and traverse speeds. In contrast to the polymeric base material, the weld zone demonstrated a lower hardness value. The heated tool induces material softening, which results in a reduction in hardness. An examination of alterations in the microstructure of the weld zone was conducted using scanning electron microscopy and stereo microscopy. The observed microstructures were applied to determine the reasons for the decrease in strength. The micrographs illustrate the formation of a fragmentation, attributable to the residual stress generated during the rapid cooling of the liquid polymer. Moreover, a highly increased temperature or traverse speed may result in the formation of voids at the joint interface.